 # deesuwalka

Members

11

• #### Last visited

• Birthday 10/17/1994

## Profile Information

• Favorite Area of Science
mathametics

## deesuwalka's Achievements 1

### Reputation

1. ## How can i check percentage problems online?

Use percent calculator- http://www.math.com/students/calculators/source/3percent.htm
2. $\int\limits^2_0 \dfrac{x^2}{x^2-2x+2} dx$ $=\int\limits^2_0 \dfrac{x^2-2x+2+2x-2}{x^2-2x+2} dx$ $=\int\limits^2_0 1+ \dfrac{2x-2}{x^2-2x+2} dx$ $=\int\limits^2_0 dx+\int\limits^2_0 \dfrac{2x-2}{x^2-2x+2} dx$ Let $t=x^2-2x+2$ $dt=(2x-2)dx$ $=\bigg[x\bigg]^2_0+\int\limits^2_0\dfrac{dt}{t}$ $=2+\bigg[\ln\,t\bigg]^2_0\;\;\implies\bigg[\ln(x^2-2x+2)\bigg]^2_0$ $=2+\bigg[\ln\,2-\ln\,2\bigg]$ $=2+0=2$
3. ## How can you move a fraction to the other side and have the same answer?

Here is the solution- $-8=\dfrac{3}{19}n$ Now, multiply both sides by $19$ $-8\times 19=\not19 \times\dfrac{3}{\not19}n$ $-152=3n$ Now, divide both sides by $3$ $\dfrac{-152}{3}=\dfrac{3n}{3}$ $\dfrac{-152}{3}=n$
4. You have to switch the $x$ and $y$, and then solve for $y$. $y=x^7+x^5$ $x=y^7+y^5$ $x=y^5(y^2+1)$ I think it can't be solved farther.
5. ## Advise a selection of books for studying of mathematics with 0.

Right, there are millions of books available. I think you should prefer online study, there are many sites which help you https://www.khanacademy.org/ http://www.mathsisfun.com/) http://www.actucation.com/
6. $\frac{x+y}{x-y}\times\frac{x-y}{x+y}$ $=\frac{\not x+\not y}{\not x-\not y}\times\frac{\not x-\not y}{\not x+\not y}$ $= 1 \times 1$ $= 1$
7. We can read the equations three types, $\frac{x- x_{1} }{ x_{2}- x_{1} } =\frac{y- y_{1} }{ y_{2}- y_{1} }$ $\frac{x- x_{1} }{ x_{2}- x_{1} } =\frac{z- z_{1} }{ z_{2}- z_{1} }$ $\frac{y- y_{1} }{ y_{2}- y_{1} }=\frac{z- z_{1} }{ z_{2}- z_{1} }$ So, I think it would be 3 equations.
8. Use order of operation, i.e.,PEMDAS (Parenthesis, Exponent, Multiplication, Division, Addition, Subtraction) $36\div 6(2+2+2)= ?$ First, Parenthesis- $=36\div6(6)$ Now, between multiplication and division, we apply operation which comes first, here division comes first so we apply division- $= 6(6)$ Now, applying multiplication- $= 6(6)\;\;\implies 6\times6=36$ I hope it' ll help.
9. We substitute $\sqrt{9-x^2}$ by $x= 3sin\theta$ because a trigonometric substitution</a> helps us to get a perfect square under the radical sign. This simplifies the integrand function.http://www.actucation.com/calculus-2/indefinite-integration/basic-methods-of-integration/integration-by-substitution-of-trigonometric-functions Now, we can simplified it easily, $\int\sqrt{9-x^2}\;\;\implies\int\sqrt{3^2-x^2}$ $\int\sqrt{3^2-x^2}\;\implies\sqrt{3^2-(3sin\theta)^2}$ $=\sqrt{9-9sin^2\theta}$ $\sqrt{9-9sin^2\theta}\;\;\implies\sqrt{9(1-sin^2\theta)}\;\;\implies\sqrt{9cos^2\theta}\;=\;\int 3cos\theta$ I hope it' ll help.
10. You can simplify it easily, $\frac{48}{2y}$ Write this as, $\frac{48}{2}\times\frac{1}{y}$ Now, simply divide 48 by 2 and then multiply, $24\times\frac{1}{y}=\frac{24}{y}$ I hope it' ll help.
11. 1. It's not an even number because it ends with 1, it's an odd number 3. It's not a prime number because it's divisible by 1,111,111 other than 1
×